Peran Hamba Tuhan Terhadap Kesehatan Mental Remaja Dalam Mencegah Anxiety Disorder di Gereja GKSI Maranatha Anugrah Sewan - Kezia Almanda Oni Eki; Martinus Sulang (BADAN PENERBIT STIEPARI PRESS, 2026)
Mental health problems, particularly anxiety disorders, are increasingly prevalent among adolescents and have become a significant concern for the church as a spiritual community. This study aims to analyze the role of God’s servants in preventing and addressing anxiety disorders among adolescents at GKSI Maranatha Anugrah Sewan, Tangerang. The research employs a qualitative method through direct observation of youth ministry activities and informal interviews with participants. The findings reveal that church ministers play a strategic role in enhancing adolescents’ mental well-being through practical biblical teaching, empathetic pastoral counseling, and the establishment of prayer and openness communities. The application of Scripture Therapy, devotional counseling, and Healing Prayer Circles has proven effective in reducing anxiety levels, strengthening spiritual security, and fostering healthy social relationships. A holistic and collaborative pastoral approach involving professional support is essential for the church to create a safe environment that promotes recovery and spiritual growth among youth